Differential actÄ±vation and expression of insulin receptor substrate 1 (IRS1) in mononuclear cells of type 2 diabetes patients after insulin stimulation - Gorgisen, G; Balci, M K; Celik, F C; Gokkaya, M; Ozdem, S; Ozel, D; Ozes, O N (Cellular and Molecular Biology, 2016)
Insulin regulates the glucose homeostasis by inducing tyrosine phosphorylation of insulin receptor substrate (IRS) proteins. IRS1 is the best studied member of this family and insulin-induced Tyrosine phosphorylation of (YXXM) motifs provides docking site for SH2 domain-containing proteins. Recent studies have suggested that genetic and/or environmental factors may affect the expression and phosphorylation levels of IRS1, and these could be important for development of insulin resistance. To shed light to the molecular basis of type 2 diabetes we wanted to determine whether YXXM motifs are genetically modified in these patients. We have isolated mononuclear cells of eighteen type 2 diabetes patients and prepared genomic DNA and protein lysates from these cells. The genomic DNA was used to sequence IRS1 gene, and protein lysates were used to determine the expression and phosphotyrosine levels of IRS1 after insulin stimulation. Although, we did not detect any mutations at/or near the YXXM coding regions in patients' DNA, immunprecipitation analysis of IRS1 indicated decreased levels of expression and tyrosine phosphorylation of IRS1 in patient's samples compared to that of healthy controls. Our results suggest that mononuclear cells of patients can be used to test the levels of insulin responsiveness before therapy.